Management of indigenous medicinal plants in Nigeria using phenological information (2014)
Available information on medicinal plants indicates habitat loss and has heightened the need for more proactive conservation strategies. Conservation efforts in this direction resulted in an eco-pharmacological survey in the West African sub-region by three countries (Nigeria, Ghana and Republic of Benin) to assess frequently used medicinal plants. The result of the socio-economic study based on utilization pattern regionally was used to produce a list of ten topmost frequently used and mentioned medicinal plants regionally and was subsequently adopted for the eco-pharmacological study in Nigeria. The list was super-imposed on a vegetation map of Nigeria for study sites selection in the species range. Selection criteria were based on the presence of at least one or more members of the medicinal plants in each location. Subsequently these plants were monitored range-wide for phenological behaviors for two seasons (dry and raining seasons) for two consecutive years. Findings indicated that the ten medicinal plants belonged to nine taxonomic families and are represented in the three plant habits. Flowering was majorly a dry season event (November to February) extending to early rains (March to April) in the species of the southern range (lowland and derived ecozones). Fruiting was typical of early rains increasing northwards (March to July). For short duration flowering species (Pcynanthus angolensis, Alstonea bonnie and Rauvolfia vomitoria), fruiting occurred late in dry season (December to February). Mean flowering duration ranged between (9.45 ± 1.73 to 45.68 ± 4.77) days, while mean fruiting duration ranged between (15.22 ± 2.15 to 145. 87 ± 8.59) days. Phenological charts were used to depict the phenological trends for the different species. The provision of this information offers a useful tool-kit for medicinal plants genetic resources monitoring, management and appropriate conservation strategies in Nigeria